The efficacy of Pembrolizumab, Ipilimumab, and Nivolumab monotherapy and combination for colorectal cancer: A systematic review and meta-analysis - Albertus Ari Adrianto; Ignatius Riwanto; Udadi Sadhana; Dewi Kartikawati Paramita; Henry Setyawan; Kevin Christian Tjandra; Danendra Rakha Putra Respati; Derren David Christian Homenta Rampengan; Roy Novri Ramadhan; Gastin Gabriel Jangkang; Endang Mahati; Patricia Winona (PLoS ONE, 2025)
Background Colorectal cancer ( CRC ) is the third leading cause of cancer-related deaths worldwide, with cases expected to rise 60% by 2030, especially in Asia. Metastatic CRC (mCRC) has a poor 5-year survival rate of 14%, posing a major treatment challenge. Tumors with DNA mismatch repair deficiency (dMMR) and a high level of microsatellite instability (MSI-H) respond well to immune checkpoint inhibitors ( ICIs ), shifting treatment strategies. This systematic review and meta-analysis evaluate Pembrolizumab (PEM), Nivolumab (NIV), and Nivolumab plus Ipilimumab (NIV + IPI) for their promising antitumor efficacy in MSI-H/dMMR mCRC. Methods This systematic review followed PRISMA guidelines and Cochrane Handbook standards, covering studies from 2014 to 2024 on advanced CRC patients treated with ICIs. A comprehensive search across eight databases was conducted by 12 independent reviewers. Extracted outcomes included overall survival ( OS ), progression-free survival ( PFS ), disease control rate ( DCR ), and objective response rate ( ORR ). To facilitate pooled analysis, data reported as median and interquartile range ( IQR ), or median, minimum, and maximum were converted to mean and standard deviation ( SD ) using combined formulas by Luo D et al. and Wan X et al. Risk of bias was assessed using the Cochrane RoB 2 tool. Meta-analyses were performed using random-effects models, with subgroup analyses by dosage. Publication bias and sensitivity analyses were conducted. All statistical analyses used RevMan version 5.4. Results A total of 13 eligible studies were analyzed, with sample sizes ranging from 11 to 307 and follow-up durations between 5.3 and 44.5 months. NIV + IPI showed the highest efficacy across all endpoints: ORR 0.54 [95% CI: 0.45–0.65, I² = 75%], OS 0.84 [95% CI: 0.81–0.88, I² = 0%], PFS 0.73 [95% CI: 0.68–0.78, I² = 0%], and DCR 0.82 [95% CI: 0.77–0.86, I² = 0%]. This combination outperformed NIV alone, which demonstrated ORR 0.36 [95% CI: 0.21–0.60, I² = 81%], OS 0.73 [95% CI: 0.62–0.86, I² = 54%], PFS 0.54 [95% CI: 0.43–0.68, I² = 34%], and DCR 0.70 [95% CI: 0.64–0.77, I² = 0%]. PEM showed lower efficacy with ORR 0.33 [95% CI: 0.23–0.49, I² = 94.6%], OS 0.59 [95% CI: 0.31–0.66, I² = 94%], PFS 0.45 [95% CI: 0.31–0.66, I² = 84%], and DCR 0.73 [95% CI: 0.47–1.12, I² = 94%]. PEM’s 200 mg dosage subgroup exhibited the best performance in its group with an ORR of 0.45 [95% CI: 0.38–0.52, I² = 0%]. Despite these findings, heterogeneity was notably high in PEM-related studies, highlighting variability in populations and study designs. Overall, NIV + IPI demonstrated superior and more consistent clinical outcomes. Conclusions This study highlights NIV + IPI as a promising combination for advanced CRC, showing superior efficacy, while PEM also demonstrated potential. However, high heterogeneity suggests the need for further research. Acknowledging its limitations, this study marks a pioneering effort in comparing short- and long-term effects of anti-CTLA-4 and anti-PD-1 therapies, paving the way for future advancements in CRC treatment.